Habilidades metafonológicas en niños de 5 años de instituciones educativas participantes y no participantes del proyecto Optimist - Callao - Romero Ortiz, Judith (2012)
The research was to compare the performance on metaphonological abilities of children 5 years of an educational institution, who led the Optimist project and the Institution that led him, in the district of Callao. It is a descriptive comparative, whose sample consisted of 72 children, the selection of the type specimen was available, who were administered the Test of metalinguistic abilities Gomez, Valero, Buades and adapted by Panca Perez (2000). To compare differences between means was used the Mann-Whitney U test and found that differences exist in all subtests of the Test for the institution that led the Optimist project.